Про когезійну зону передруйнування біля вершини міжфазної тріщини, що виходить з кутової точки ламаної межі поділу матеріалів - Камінський, А.О.; Дудик, М.В.; Решітник, Ю.В. (Доповіді НАН України, 2020)
В рамках когезійної моделі побудовано розв'язок задачі про розрахунок параметрів зони передруйнування
у з'єднувальному матеріалі в кінці міжфазної тріщини, що виходить з кутової точки ламаної межі поділу
двох різних однорідних ізотропних матеріалів. Зона моделюється лінією розриву переміщення, на якій напруження задовольняють критерій міцності Мізеса—Хілла. Отримано рівняння для визначення довжини
зони передруйнування i фазового кута напруження в зоні та вираз для розкриття тріщини в її вершині. Within the framework of the cohesion model, the solution of the problem of calculating the parameters of the
pre-fracture zone in a joining material at the end of an interfacial crack propagating from the corner point of
the broken interface of the two different homogeneous isotropic materials is obtained. The zone is modeled by
the discontinuity line of displacements, on which the stresses meet the Mises—Hill strength criterion. By the
Mellin integral transformation, the problem is reduced to the Wiener—Hopf vector equation. An approximate
method of solution of the Wiener—Hopf vector equation is proposed. The method is based on the representation
of the matrix coefficient of the equation in the form of a sum of two matrices, one of which allows for an exact
factorization, while the other one is considered as a small perturbation to the first one. The solution of the equation
is searched in the form of expansions by the degrees of a matrix-perturbation. From the found solution,
the equations for calculating the pre-fracture zone length and the phase angle of stress in the zone, and the expression
for the crack opening at the tip are obtained. В рамках когезионной модели построено решение задачи о расчете параметров зоны предразрушения в
связующем материале в конце межфазной трещины, выходящей из угловой точки ломаной границы раздела двух различных однородных изотропных материалов. Зона моделируется линией разрыва перемещения, на которой напряжения удовлетворяют критерий прочности Мизеса—Хилла. Получены уравнения для расчета длины зоны предразрушения и фазового угла напряжения в зоне, а также выражение для раскрытия трещины в ее вершине.